The synergy of methylphenidate- and reconsolidation-based extinction normalizes ventromedial prefrontal function in drug addiction - Ahmet O. Ceceli; Sarah G. King; K. Rachel Drury; Natalie McClain; John Gray; Priyanthi S. Dassanayake; Jeffrey H. Newcorn; Daniela Schiller; Nelly Alia-Klein; Rita Z. Goldstein (Proceedings of the National Academy of Sciences, 2025)
Drug-related memories can hinder abstinence goals in drug addiction. Promoting nondrugmemories via ventromedial prefrontal cortex (vmPFC)- and amygdala-guided extinctionyields mixed success. Postretrieval extinction (RE) destabilizes and updates memoriesduring reconsolidation, improving extinction. Supplementing RE, we tested methylphenidate(MPH), a dopamine agonist that promotes PFC-dependent learning and memory in cocaineuse disorder (CUD). In a proof-of-concept double-blind randomized clinical trialusing a within-subjects design, participants received oral MPH (20 mg) or placebobefore the retrieval of some of the conditioned stimuli (CS) (i.e., reminded CS+ vs.nonreminded CS+) followed by extinction; lab-simulated drug-seeking was measuredthe following day. Lower vmPFC activity following nonreminded CS+ (standardextinction) under placebo replicated the putative impairments in CUD; separately, RE (trend) and MPH conditions recruited the vmPFC, and RE’s vmPFC-reliance correlatedwith drug-seeking only under placebo. Crucially, MPH-combined RE normalized cortico-limbicprocessing, bypassing the vmPFC and its amygdala connectivity. Pharmacologically-enhanced drug memory modulation may inform intervention development for addictionrecovery.